Analisis Persepsi, Preferensi, dan Ekspektasi Perancangan Children Playground Panti Asuhan Salib Putih Salatiga - Setiyawan, Yeni; Pudjihartati, Endang (Jurnal Arsitektur Lansekap; Vol.7, No.2, Oktober 2021, 2021)
Analysis of perceptions, preferences, and expectations for the design of the children playground at the Salib Putih Orphanage in Salatiga. Playing is a need for children that must be fulfilled. Children can improve gross and fine motoric development, improve reasoning, and understand their environment, shape their imagination, fantasy power, and creativity by playing. At this time, the Salib Putih Orphanage did not have a special play area for children, the children play in the yard and hall. This study aims to determine the potential and constraints on the site of the Salib Putih Orphanage and to determine the perceptions, preferences, and expectations of stakeholders in the orphanage regarding the design of the children playground which can then be used as input in designing the play area at the Salib Putih Orphanage. The research stages included site surveys, interviews with orphanage caregivers and foundation administrators as well as questionnaires to 40 respondents covering the residents of orphanages, the children and adolescents, with educational levels ranging from elementary school, junior high school to higher education, the orphanage foundation staff and workers, also the practical students at the orphanage. Site survey includes location, boundaries, accessibility, climate. Interviews use the in-depth interview method, which is the process of extracting information in depth, openly, and free of problems and research focus, while the questionnaire for respondents using the Likert measurement scale is presented with several questions that must be filled, given 5 choices that have gradations levels from Strongly Disagree, Disagree, Neutral, Agree to Strongly Agree. Each of these answer choices has a weighted value of 1-5 points. The results showed that the site in the area of the Salib Putih Orphanage has the potential to build a children’s playground with a variety of facilities and supports in accordance with the analysis of perceptions, preferences, and expectations.